Community Education on the Prevention and Control of Dengue Hemorrhagic Fever (DHF) at Pujidadi Sub-Health Center, Binjai City, 2025 - Amenda Paswida Sebayang (Outline Journal of Community Development, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health challenge in Indonesia, particularly in densely populated areas with low awareness of environmental disease prevention. This community service activity aimed to increase public knowledge and awareness regarding the prevention and control of DHF through health education and counseling in the working area of the Pujidadi Sub-Health Center, Binjai City. The activity was conducted by lecturers from the Master of Public Health Program, Institute of Health Sciences of North Sumatra (INKESSUMUT), as part of the 2024 community service program organized by the Institute for Research and Community Service (LPPM) INKESSUMUT. Methods included interactive lectures, small group discussions, and practical simulations of mosquito breeding site eradication (PSN) using the 3M Plus approach. Educational materials such as leaflets, posters, and visual aids were used to support learning. Target participants included housewives, health cadres, and local youth. The results showed improved community understanding of DHF symptoms, transmission methods, and the importance of maintaining environmental cleanliness as a preventive measure. Participants demonstrated high enthusiasm and expressed commitment to adopting clean and healthy living behaviors (PHBS) and continuing PSN activities regularly. This initiative highlights the effectiveness of community-based educational approaches in enhancing disease prevention efforts and represents a practical implementation of the Tri Dharma of Higher Education in improving public health.